Optimization of turbidity and dye removal from synthetic wastewater using response surface methodology: effectiveness of Moringa oleifera seed powder as a green coagulant - El Gaayda, Jamila; Titchou, Fatima Ezzahra; Barra, Issam; Karmal, Ilham; Afanga, Hanane; Zazou, Hicham; Yap, Pow-Seng; Zainal Abidin, Zurina; Mohamed Hamdani; Akbour, Rachid Ait (Elsevier, 2022)
The present work evaluated the efficiency of Moringa oleifera seed powder (MOSP) as a natural coagulant for removing both turbidity and anionic dye from synthetic wastewater. The bio-coagulation tests were performed by preparing synthetic wastewater containing high turbidity and Amido Black 10B dye. The efficiency of MOSP treatment was optimized using the central composite design (CCD) based on response surface methodology (RSM) and statistical analysis. A series of experiments were conducted to study the influence of several parameters on the coagulation efficiency, namely dosage of MOSP, initial dye concentration, pH, settling time, stirring speed, and stirring time. Experimental results indicated that the removal efficiencies of turbidity and dye from the synthetic wastewater achieved 98.5% and 92.2%, respectively. Numerical optimization results demonstrated that removal efficiencies of turbidity and dye of 100% were obtained at the optimum conditions as follows: MOSP dosage (0.34 mg L−1), dye concentration (7.88 mg L−1), initial pH (6.93), settling time (113.15 min), stirring speed (135 rpm), and stirring time (13.52 min). Moreover, the mechanism of removing turbidity and Amido Black 10B dye by MOSP could be attributed to surficial adsorption due to electrostatic interactions and hydrogen bonding effects. The results obtained have proven that MOSP bio-coagulant could be used as an efficient natural substance for wastewater treatment and an alternative to chemical coagulants.